The Relationship between Listening Anxiety Among Iraqi EFL University Students' and their Performance in Listening Comprehension - Ali, Alaa; Hameed, Dunia Tahir (جامعة كركوك, 2020)
تهتم الدراسة الحالية بالعلاقة بين قلق الاستماع لدى طلبة الجامعة العراقيين دارسي اللغة الإنكليزية لغة أجنبية وأدائهم في فهم الاستماع. يعتبر قلق الاستماع عامل مؤثر في تعلم اللغة الأجنبية ويلعب دور مهم في فهم الاستماع إلى اللغة الأجنبية. تهدف الدراسة الحالية إلى تطوير مهارات فهم الاستماع لدارسي اللغة الإنكليزية كلغة أجنبية والكشف عن مشاكل قلق الاستماع لديهم. تتألف عينة هذه الدراسة من (131) طالبا "وطالبة" من المرحلة الأولى والثالثة في قسم اللغة الإنكليزية كلية التربية للعلوم الإنسانية خلال السنة الدراسية 2018- 2019. لتحقيق أهداف هذه الدراسة بنيت أداتين، مقياس قلق الاستماع والفهم والاستماع. حيث تشير النتائج إلى وجود درجه عالية من قلق الاستماع لدى طلبة الجامعة العراقيين دارسي اللغة الإنكليزية لغة أجنبية وأداء منخفض في فهم الاستماع.
The present research is concerned with the relationship between listening anxiety among Iraqi EFL university Students’ and their performance in listening comprehension. Listening anxiety is considered an influential factor in foreign language learning and plays a crucial role in foreign language listening comprehension skill. The present research aims at developing the EFL Listening comprehension skill which is necessary for the Iraqi EFL University Students and find out anxiety problems The sample of the present research consists of 131 male and female students from the first and third stages at English Department / College of Education for Humanities university of Tikrit during the academic year 2018 /2019. To achieve the aims of the research, two instruments have been constructed: a listening anxiety scale and a listening comprehension skill. Result shows that Iraqi EFL students' have a high degree of listening anxiety and they low performance in listening comprehension.
Keywords: الاضطرابات النفسية -- قلق الاستماع -- اللغة الإنجليزية -- طلبة الجامعات -- العراق